AMORPHOLOGICAL STUDY ON THE USE OF REVERSED WORDS IN BALINESE LANGUAGE USED BY THE PEOPLE IN TIANYAR TIMUR - ., Ni Made Astiti Sari; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Dewa Putu Ramendra, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini berusaha untuk menggambarkan bentuk kata terbalik digunakan oleh orang-orang di Tianyar Timur dalam proses morfologi dan untuk menggambarkan fungsi kata terbalik dalam percakapan sehari-hari. Obyek penelitian terbalik kata-kata sebuah studi morfologi dilakukan dalam bahasa Bali yang digunakan dalam Tianyar Timur. Mereka adalah tiga jenis pembentukan kata yang ditemukan dalam kata-kata terbalik yang digunakan dalam Tianyar Timur: 1) tipe pertama pembentukan kata dibentuk dengan mengucapkan suku kata dari kata dari suku kata kembali ke suku kata depan, 2) jenis kedua kata formasi dibentuk dengan mengucapkan huruf dari kata dari huruf terakhir dengan huruf depan, 3) jenis ketiga adalah suara vokal: A, I, U, E, O, e yang konstanta, dan suara konsonan harus diubah menjadi: BJ, CD, F, P, V NY, GW, HR, Q, KN, LT, Y NG, MS, Z. Kata akan berubah karena; kata ini memiliki suara yang sama dan suara dari kata yang penting. Kata Kunci : Kata Terbalik, studi morfologi, Pidato Community. ABSTRACT This study attempted to describe the forms of the reversed word used by people in Tianyar timur in morphological process and to describe the function of the reversed word in daily conversation. The objects of study were reversed words a morphological study conducted in the Balinese language used in Tianyar Timur. They were three types of word formation found in the reversed words used in Tianyar Timur: 1) the first type of word formation was formed by uttering the syllable of the word from the back syllable to the front syllable, 2) the second type of word formation was formed by uttering the letter of the word from the last letter to the front letter, 3) the third type is the vocal sound: A,I,U,E,O,e are constants, and the consonant sound must be changed to become: B J, C D, F,P,V NY, G W, H R, Q,K N, L T, Y NG, M S,Z. The word changes because; this word has a same sound and the sound of the word which is important. Key Words: Reversed word , Morphological study, Speech Community. keyword : Key Words: Reversed words , Morphological study, Speech Community